Utilizing Spatial Multi-Criteria Evaluation for Analyzing Physical and Social Vulnerability at Merapi Volcano - Hermawan, Hannan Revi; Hizbaron, Dyah Rahmawati (JURNAL GEOGRAFI, 2025)
Merapi Volcano is one of the most active volcanoes in Indonesia, which poses a primary eruption hazard in the form of pyroclastic flows. Pakem District is one of the areas affected by the eruption. Vulnerability is the situation where a community experiences a decrease in resilience due to a threatening event that jeopardizes their survival and livelihood. Vulnerability analysis aims to reduce disaster risk. The purpose of this research is to map and analyze the social, physical, and total vulnerability resulting from the eruption of Merapi  Volcano in Pakem District using the SMCE method. This research employs the Spatial Multi Criteria Evaluation (SMCE) method to create scenarios based on specific criteria. The results indicate that each village has various classifications of social and physical vulnerability classes. Population density is the most significant variable affecting social vulnerability, whereas the estimated losses from housing damage are the most significant variable influencing physical vulnerability. The results of total vulnerability scenarios, including social, physical, and equal, show the same and consistent class classifications. Candibinangun Village, Harjobinangun Village, and Pakembinangun Village are classified as low total vulnerability. Meanwhile, Hargobinangun Village is classified as low and medium total vulnerability, while Purwobinangun Village is classified as low, medium, and high total vulnerability.